HUBUNGAN KEKERABATAN ANTARA BAHASA TIDUNG, BAHASA KUTAI, DAN BAHASA BANJAR - Nur Bety (Kantor Bahasa Kalimantan Timur, 2016)
All this time, some communities assume that Tidung language is a part of Melayu Kutai or Melayu Banjar language. However, there is still an opinion saying that Tidung language is a separate language. This research of kinship among Tidung, Kutai, and Banjar languages aims to know the kinship level of these three languages. It uses comparative-historical method and the technique of lexicostatistics is also adopted. The data is Swadesh 200-word list. The result reveals that there were close relations of kinship attributed to the cognate percentages by 73% between Kutai and Banjar language, by 34% between Tidung and Kutai language, and by 31% between Tidung and Kutai language. It also shows allophones on several cognates among these languages.